Epidemiological data on LCL and PCL injuries over 17 seasons in men`s professional soccer: The UEFA elite club injury study - Lundblad, M.; Hägglund, M.; Thomeé, C.; Hamrin Senorski, E.; Ekstrand, J.; Karlsson, J.; Waldén, M. (Open Access Journal of Sports Medicine, 2020)
Background: There is limited epidemiological information on injury rates and injury mechanisms for lateral collateral ligament (LCL) and posterior cruciate ligament (PCL) injuries in male professional soccer. In addition, time trends and lay-off times for these injuries have not yet been determined. Aim: To determine injury rates and circumstances of LCL and PCL injuries over 17 seasons in men`s professional soccer. Methods: A prospective cohort study, in which 68 professional European soccer teams were followed over 17 consecutive seasons (2001/2002 to 2017/2018). The teams` medical staff recorded player exposure and time-loss injuries. Lay-off time was reported as the median and the first and third quartile. Injury rate was defined as the number of injuries per 1000 player-hours. Results: One hundred and twenty-eight LCL and 28 PCL injuries occurred during 2,554,686 h of exposure (rate 0.05 and 0.01/1000 h, respectively). The median lay-off time for LCL injuries was 15 (Q1=7, Q3=32) days, while it was 31 days for PCL injuries (Q1=15, Q3=74). The match injury rate for LCL injuries was 11 times higher than the training injury rate (0.21 vs 0.02/1000 h, rate ratio [RR] 10.5, 95% CI 7.3 to 15.1 p< 0.001) and the match injury rate for PCL injuries was 20 times higher than the training injury rate (0.056 vs 0.003/1000 h, RR 20.1, 95% CI 8.2 to 49.6, p< 0.001). LCL injuries saw a significant annual decrease of approximately 3.5% (p=0.006). In total, 58% (63/108) of all LCL injuries and 54% (14/26) of all PCL injuries were related to contact mechanism. Conclusion: This study with prospectively registered data on LCL and PCL injuries in men`s professional soccer shows that the median lay-off from soccer for LCL and PCL injuries is approximately 2 and 4 weeks respectively. These rare knee ligament injuries typically occur during matches and are associated with a contact injury mechanism.